Експортна стратегія українських виробників будівельних матеріалів в умовах воєнного стану - Восканян Норік Геворгович (My University, 2023)
Мета дипломної роботи - узагальнення теоретичних підходів та розробка практичних рекомендацій щодо вибору оптимальної експортної стратегії виходу українських виробників будівельних матеріалів на міжнародні ринки в умовах воєнного стану. Об’єктом дослідження виступає ринкова діяльність українських виробників будівельних матеріалів на міжнародних ринках в умовах військової агресії з боку РФ. Предметом дослідження є теоретичні та практичні аспекти вибору експортної стратегії українських виробників будівельних матеріалів на міжнародних ринках. За результатами дослідження сформульовані рекомендації щодо ефективної експортні стратегії ТОВ «Технобуд Груп» на ринку будівельних матеріалів Польщі. Одержані результати та висновки можуть бути використані будівельними компаніями для прибуткової діяльності на Польському ринку будівельних матеріалів.

The object of the research is the market activity of Ukrainian manufacturers of building materials on international markets in the conditions of military aggression by the Russian Federation. The subject of the study is the export strategy of Technobud Group LLC on the Polish building materials market. The purpose of the thesis is to develop export strategies of Technobud Group LLC in the Polish building materials market, which will allow the company to increase sales and profits, as well as improve competitiveness in foreign sales markets. Based on the results of the research, recommendations were formulated regarding the effective export strategy of Technobud Group LLC on the construction materials market in Poland. The obtained results and conclusions can be used by construction companies for profitable activities on the Polish market of building materials.
Export strategy of Ukrainian manufacturers of building materials under martial law